2012
DOI: 10.1097/mca.0b013e32834df5d0
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea is common among patients referred for coronary artery bypass grafting and can be diagnosed by portable monitoring

Abstract: 2012Obstructive sleep apnea is common among patients referred for coronary artery bypass grafting and can be diagnosed by portable monitoring CORONARY ARTERY DISEASE, PHILADELPHIA, v. 23, n. 1, supl. 2, Part 3, pp. 31-38, JAN, 2012 http://www.producao.usp.br/handle/BDPI/32565 Downloaded from: Biblioteca Digital da Produção Intelectual -BDPI, Universidade de São Paulo Biblioteca Digital da Produção Intelectual -BDPI Outros departamentos -FM/Outros Comunicações em Eventos -FM/OutrosObstructive sleep apnea is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 36 publications
(72 reference statements)
2
25
0
2
Order By: Relevance
“…These studies were conducted in China, Brazil, Croatia, Turkey and the United States, thus reflecting a wide geographic sampling. 38,43,50,51,[59][60][61] Participants were those suspected of OSA and included mainly male, middle-aged and overweight or obese individuals. The overall results indicate that the ESS had a large number of false negative results limiting its utility for the diagnosis of OSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were conducted in China, Brazil, Croatia, Turkey and the United States, thus reflecting a wide geographic sampling. 38,43,50,51,[59][60][61] Participants were those suspected of OSA and included mainly male, middle-aged and overweight or obese individuals. The overall results indicate that the ESS had a large number of false negative results limiting its utility for the diagnosis of OSA.…”
Section: Discussionmentioning
confidence: 99%
“…33 Our review identified nineteen studies that evaluated the performance of the Berlin Questionnaire against PSG in the identification of patients with OSA. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] The studies were conducted in a wide variety of geographic locations including Brazil, 38 Canada, 34,42 Greece, 37 Iran, 36 Korea, 40 Turkey, 43 and the United States. 41,44 Various patient populations were considered, including those in primary care clinics, sleep clinics, the veteran population, and patients with cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…32 Yet, in real-world clinical practice, significantly more patients undergo coronary revascularization with percutaneous coronary intervention than coronary artery bypass surgery. Therefore, the excluded surgical candidates constituted a small proportion of CAD patients, and the OSA prevalence reported in this study should be very close to the actual prevalence among all patients presenting with symptomatic CAD.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2006;DANZI-SOARES et al, 2012;MUNGAN et al, 2013). Segundo a Academia Americana de Medicina do Sono (AASM) (2015), sua incidência é 2 a 3 vezes maior em pacientes com doenças cardiovasculares e sua prevalência gira em torno de 50% nesta população de doentes.…”
Section: Introductionunclassified